Recent advances of traditional Chinese medicine against cardiovascular disease: overview and potential mechanisms - Dai, Junting; Qiu, Lulu; Lu, Yi; Li, Miao (Frontiers in Endocrinology, 2024)
Cardiovascular disease (CVD) is the leading cause of human mortality worldwide. Despite Western medicine having made encouraging results in the clinical management of CVD, the morbidity, mortality, and disability rates of the disease remain high. Modern pharmacology has confirmed that traditional Chinese medicine (TCM), characterized by its multi-component, multi-target, and integrity, plays a positive and important role in the prevention and treatment of various CVDs in China, which has notable advantages in stabilizing disease, improving heart function, and enhancing the quality of life. Importantly, TCM is gradually being accepted by the international community due to its low cost, high safety, versatile bioactivity, and low toxicity. Unfortunately, comprehensive studies on the therapeutic effect of TCM on CVD and its mechanisms are very limited, which may restrict the clinical application of TCM in CVD. Therefore, this review is performed to analyze the pathogenesis of CVD, including inflammatory response, oxidative stress, mitochondrial dysfunction, pyroptosis, ferroptosis, dysbiosis of gut microbiota, etc. Moreover, we summarized the latest progress of TCM (formulas, extracts, and compounds) in curing CVD according to published literature from 2018 to 2023, as well as its mechanisms and clinical evidence. In conclusion, this review is expected to provide useful information and reference for the clinical application of TCM in the prevention and treatment of CVD and further drug development of CVD.